ISLAM RAHMATAN LIL ALAMIN AND THE ROLE OF DA'WAH IN BUILDING SOCIAL HARMONY IN THE ERA OF GLOBALIZATION - Gunawan, Chandra; Sirojuddin, Sirojuddin; Yasin, Rahman (Spektra: Jurnal Ilmu-ilmu Sosial, 2025)
Islam Rahmatan Lil Alamin is a concept that affirms that Islam exists as a blessing for the entire universe, including humans, animals, and the environment. In the era of globalization, this principle has become relevant to strengthen social harmony in the midst of plurality of society. This article aims to analyze how Islamic da'wah based on Rahmatan Lil Alamin can be an effective means of building social harmony in the global era. Using a qualitative approach and literature study, this article discusses moderate da'wah strategies, principles of social justice, and tolerance between religious communities. The results of the study show that Islamic da' wah Rahmatan Lil Alamin plays an important role in strengthening religious moderation, reducing the potential for social conflicts, and promoting the values of compassion and justice for all elements of society. This finding strengthens the urgency of integrating the concept of Rahmatan Lil Alamin in contemporary da'wah strategies in order to maintain social harmony.